Exercise-Induced Release of Cardiac Troponins in Adolescent vs. Adult Swimmers - Cirer Sastre, Rafel; Corbi, Francisco; López Laval, Isaac; Carranza García, Luis Enrique; Reverter Masía, Joaquín (Molecular Diversity Preservation International, 2021)
To examine the exercise-induced release of cardiac troponin T (cTnT) in adolescent and adult swimmers. Thirty-two trained male (18 adolescents, 14 adults) swam at maximal pace in a 45 min distance trial, and blood samples were drawn before, immediately and 3 h after exercise for subsequent cTnT analysis and comparison. Having comparable training experience and baseline values of cTnT (p = 0.78 and p = 0.13), adults exercised at lower absolute and relative intensity (p p p p = 0.074). Fourteen (44%) apparently healthy subjects exceeded the cutoff value for myocardial infarction (MI). Adolescents presented a delayed elevation of cTnT compared with adults, but achieved similar peak values.